Functional trait data for vascular plant species from northeastern North America. Issue 1 (13th December 2021) - Waller, Donald M.; Paulson, Alison K.; Richards, Jeannine H.; Alverson, William S.; Amatangelo, Kathryn L.; Bai, Chengke; Johnson, Sarah E.; Li, Daijiang; Sonnier, Grégory; Toczydlowski, Rachel H.
Abstract: Wisconsin's plant communities are responding to shifting disturbance regimes, habitat fragmentation, aerial nitrogen deposition, exotic species invasions, ungulate herbivory, and successional processes. To better understand how plant functional traits mediate species' responses to changing environmental conditions, we collected a large set of functional trait data for vascular plant species occupying Wisconsin forests and grasslands. We used standard protocols to make 76, 213 measurements of 34 quantitative traits. These data provide rich information on genome size, physical leaf traits (length, width, circularity, thickness, dry matter content, specific leaf area, etc.), chemical leaf traits (carbon, nitrogen, phosphorus, potassium, calcium, magnesium, ash), life history traits (vegetative and flower heights, seed mass), and traits affecting plant palatability (leaf fiber, fat, and lignin). These trait values derive from replicate measurements on 12+ individuals of each species from multiple sites and 45+ individuals for a selected subset of species. Measurements typically reflect values for individuals although some chemical traits involved composite samples from several individuals at the same site. We also qualitatively characterized each species by plant family, woodiness, functional group, and Raunkiaer lifeform. These data allow us to characterize trait dimensionality, differentiation, and covariation among temperate plant species (e.g., leaf and stem economic syndromes). We can also characterize species' responses to environmental gradients and drivers of ecological change. With survey and resurvey data available from >400 sites in Wisconsin, we can analyze variation in community trait distributions and diversity over time and space. These data therefore allow us to assess how trait divergence vs. convergence affects community assembly and how traits may be related to half‐century shifts in the distribution and abundance of these species. The data set can be used for non‐commercial purposes. The data set is licensed as follows: CC‐By Attribution 4.0 International. We request users cite both the OSF data set and this Ecology data paper publication.